Factors shaping political priorities for violence against women-mitigation policies in Sri Lanka - Manuela Colombini; Susannah H Mayhew; Ragnhild Lund; Navpreet Singh; Katarina Swahnberg; Jennifer Infanti; Berit Schei; Kumudu Wijewardene (BMC, 2018)
Abstract Background Although violence against women (VAW) is a global public health issue, its importance as a health issue is often unrecognized in legal and health policy documents. This paper uses Sri Lanka as a case study to explore the factors influencing the national policy response to VAW, particularly by the health sector. Methods A document based health policy analysis was conducted to examine current policy responses to VAW in Sri Lanka using the Shiffman and Smith (2007) policy analysis framework. Results The findings suggest that the networks and influences of various actors in Sri Lanka, and their ideas used to frame the issue of VAW, have been particularly important in shaping the nature of the policy response to date. The Ministry of Women and Child Affairs led the national response on VAW, but suffered from limited financial and political support. Results also suggest that there was low engagement by the health sector in the initial policy response to VAW in Sri Lanka, which focused primarily on criminal legislation, following global influences. Furthermore, a lack of empirical data on VAW has impeded its promotion as a health policy issue, despite financial support from international organisations enabling an initial health systems response by the Ministry of Health. Until a legal framework was established (2005), the political context provided limited opportunities for VAW to also be construed as a health issue. It was only then that the Ministry of Health got legitimacy to institutionalise VAW services. Conclusion Nearly a decade later, a change in government has led to a new national plan on VAW, giving a clear role to the health sector in the fight against VAW. High-level political will, criminalisation of violence, coalesced women's groups advocating for legislative change, prevalence data, and financial support from influential institutions are all critical elements helping frame violence as a national public health issue.